How the planned perversion of democracy generated accelerating inequalities - Alain Parguez (Journal of Contemporary Economic and Business Issues, 2016)
One cannot doubt the ubiquitous lack of hope and confidence in the so-called democratic institutions by the large majority of people. The fundamental reason thereof is the blatant contradiction between the principle of democracy, promoting the rule of law and thereby the welfare of people, and the indomitable tendency of rising and unsustainable inequality in terms of income, standard of living and wealth. All studies display the same dire outcome: a concentration of income and wealth in a tiny minority, a genuine ruling class, the famous one percent of predator barons of the gilded age, and even for Europe, of the pre-revolution era2. What is at stake is to understand the paramount failure of political institutions to meet the essential of democracy. It could be a road to genuine reforms3 preventing a disaster caused by the sheer rejection of democratic institutions bringing misery without hope of a better future.
Keywords: D60; D63; D70; D78; 330; democracy; inequality; political institutions; capitalist system